2019
DOI: 10.12973/eujem.2.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Freedom to Choose within Limits: Teacher Autonomy from the Perspectives of Basic School Teachers in Ghana

Abstract: The study examined the level of autonomy among basic school teachers in the Central Region of Ghana and the effect of teacher demographic characteristics on the level of teacher autonomy. The explanatory sequential design was adopted. Using the systematic sampling technique, a total of 315 basic school teachers were sampled for the quantitative phase of the study whilst 12 teachers were sampled for the qualitative phase through the purposive sampling technique. Eighteen (18) Likert-scale items were adapted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It can be asserted that teachers have a high sense of autonomy even when they experience frustration from different sources (Einolf, 2002;Rudolf, 2006). While some studies on teacher autonomy yielded that the teachers had a moderate level of autonomy perception (Çolak & Altınkurt 2017;Dampson et al, 2019), some others reported a high level of autonomy perception (Salokangas et al, 2020;Yorulmaz et al, 2018). The divergent results of the studies may be related to the factors such as school climate, school culture, administrative approach, the processes of teacher training and development.…”
Section: Discussionmentioning
confidence: 99%
“…It can be asserted that teachers have a high sense of autonomy even when they experience frustration from different sources (Einolf, 2002;Rudolf, 2006). While some studies on teacher autonomy yielded that the teachers had a moderate level of autonomy perception (Çolak & Altınkurt 2017;Dampson et al, 2019), some others reported a high level of autonomy perception (Salokangas et al, 2020;Yorulmaz et al, 2018). The divergent results of the studies may be related to the factors such as school climate, school culture, administrative approach, the processes of teacher training and development.…”
Section: Discussionmentioning
confidence: 99%